2014
DOI: 10.1093/nar/gku913
|View full text |Cite
|
Sign up to set email alerts
|

The Werner syndrome protein limits the error-prone 8-oxo-dG lesion bypass activity of human DNA polymerase kappa

Abstract: Human DNA polymerase kappa (hpol κ) is the only Y-family member to preferentially insert dAMP opposite 7,8-dihydro-8-oxo-2′-deoxyguanosine (8-oxo-dG) during translesion DNA synthesis. We have studied the mechanism of action by which hpol κ activity is modulated by the Werner syndrome protein (WRN), a RecQ helicase known to influence repair of 8-oxo-dG. Here we show that WRN stimulates the 8-oxo-dG bypass activity of hpol κ in vitro by enhancing the correct base insertion opposite the lesion, as well as extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Similar to BLM, WRN is recruited at stalled replication forks, and it is able to catalyze in vitro fork regression as well as conversion of regressed HJs to functional forks (Constantinou et al, 2000; Machwe et al, 2011). Additionally, WRN is able to stimulate the bypass of DNA damage by translesion polymerases, which are specialized polymerases that are able to replicate across damaged DNA, a function that BLM has not been reported to have (Kamath-Loeb et al, 2007; Maddukuri et al, 2014; Maddukuri et al, 2012; Phillips and Sale, 2010). …”
Section: Blm Functions In Dna Transactionsmentioning
confidence: 99%
“…Similar to BLM, WRN is recruited at stalled replication forks, and it is able to catalyze in vitro fork regression as well as conversion of regressed HJs to functional forks (Constantinou et al, 2000; Machwe et al, 2011). Additionally, WRN is able to stimulate the bypass of DNA damage by translesion polymerases, which are specialized polymerases that are able to replicate across damaged DNA, a function that BLM has not been reported to have (Kamath-Loeb et al, 2007; Maddukuri et al, 2014; Maddukuri et al, 2012; Phillips and Sale, 2010). …”
Section: Blm Functions In Dna Transactionsmentioning
confidence: 99%
“…WRN interacts with several DNA pols (pol δ [163165] and translesion DNA pols [12,166]) to stimulate DNA synthesis and improve fidelity via WRN’s 3′–5′exonuclease activity. WRN is recruited to stalled replication forks to aid in fork recovery and restart [126,167172].…”
Section: Protein Interactions and Genome Maintenance Pathwaysmentioning
confidence: 99%
“…Although some studies showed that elevated Pol κ promotes genomic instability [5], other studies showed that Pol κ protects cells from mutagens [10,11] and that Pol κ deficiency may exacerbate mutagenesis [12,13]. Interestingly, studies also demonstrated that Pol κ participates in processing of different types of oxidative lesions, including strand breaks [14], bypass of 8-oxo-dG [15] and abasic sites [16,8], which are base excision repair (BER) substrates, as well as processing of bulky lesions that are substrates of the nucleotide excision repair (NER) pathway [17,18]. This suggests that in neurons, Pol κ might have a role in repair of diverse lesions, including cisplatin:DNA crosslinks, which are typical NER substrates [19] and in fact, cells lacking Pol κ are partially defective in interstrand crosslink removal [20,21].…”
Section: Introductionmentioning
confidence: 99%